Evaluation on teaching English simple future tense on grade 7 at SMP Tunas Harapan Pasar Kemis - Dwi Indarti; Baiatun Nisa (Mitra Palupi, 2021)
Background: Teaching languages has different ways from teaching another subjects. Purpose: The objective of this research is to know the effectiveness of Active Learning Method in Teaching Simple Future. Design and methods: This research is using an evaluation method. The research was conducted at the seventh grade of SMP Tunas Harapan, Pasar Kemis, Tangerang. The data were collected through observation, teaching learning process, pre-test and post-test, questionnaires. This program contains the planning, how to implement and improve the students’ English Grammar Simple Future through Active Learning Method. The exercise was a mean to evaluate the action conducted in research. Results: The result of this research indicated that: (1) Using Active Learning Method in teaching simple future is one of a good solution to improve the students’ grammar skill, (2) it makes students are more easily in understanding and using simple future tense in daily activities, and (3) students become more active in responding the lessons or questions given by the teacher.